New insights into nucleolar architecture and activity - Raska, Ivan; Shaw, Peter J; Cmarko, Dusan (International review of cytology, 2006)
The nucleolus is the most obvious and clearly differentiated nuclear subcompartment. It is where ribosome biogenesis takes place and has been the subject of research over many decades. In recent years progress in our understanding of ribosome biogenesis has been rapid and is accelerating. This review discusses current understanding of how the biochemical processes of ribosome biosynthesis relate to an observable nucleolar structure. Emerging evidence is also described that points to other, unconventional roles for the nucleolus, particularly in the biogenesis of other RNA-containing cellular machinery, and in stress sensing and the control of cellular activity. Striking recent observations show that the nucleolus and its components are highly dynamic, and that the steady state structure observed by microscopical methods must be interpreted as the product of these dynamic processes. We still do not have detailed enough information to understand fully the organization and regulation of the various processes taking place in the nucleolus. However, the present power of light and electron microscopy (EM) techniques means that a description of nucleolar processes at the molecular level is now achievable, and the time is ripe for such an effort.
Keywords: oxidační stres; dějiny 20. století; telomerasa; Neoplasms; History, 21st Century; Cell Nucleolus; biologie buňky; Protein Biosynthesis; proteosyntéza; Mitosis; Nucleolus Organizer Region; nádorový supresorový protein p53; ribozomy; buněčné jadérko; elektronová mikroskopie; Ribosomes; Animals; RNA, Nuclear; lidé; signál-rozpoznávající částice; RNA; History, 20th Century; Telomerase; organizátor jadérka; Humans; zvířata; Microscopy, Electron; Tumor Suppressor Protein p53; Cell Cycle; nádory; mitóza; buněčný cyklus; RNA jaderná; Oxidative Stress; dějiny 21. století; Signal Recognition Particle; Cell Biology